2011
DOI: 10.4067/s0718-16202011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of harvest maturity of D'Agen plums using the chlorophyll absorbance index

Abstract: The objective determination of the optimal harvest date for plums intended either for industrial processing or for consumption as fresh fruit is a fundamental concern of the fruit industry. A portable visible/near infrared (Vis/NIR) spectroscopic device was used to sort D'Agen plums harvested around the traditional commercial harvest date. The chlorophyll absorbance index was found to be capable of segregating plums into classes of maturity according to various concentrations of soluble solids and fruit compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…In fact, a relatively low correlation ( 2 = 0.60) between AD and SSC was observed (Figure 3). These results were also in agreement with Hale et al [40] for "August Fire" but in contrast to a recent publication by Infante et al [18] on two cultivars of Japanese plums, "Angeleno" and "Autumn Beauty". Infante [41] described the AD as an index having high correlation with the most common parameters used for monitoring ripening, such as fruit firmness and SSC with 2 > 0.89 and >0.70, respectively.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In fact, a relatively low correlation ( 2 = 0.60) between AD and SSC was observed (Figure 3). These results were also in agreement with Hale et al [40] for "August Fire" but in contrast to a recent publication by Infante et al [18] on two cultivars of Japanese plums, "Angeleno" and "Autumn Beauty". Infante [41] described the AD as an index having high correlation with the most common parameters used for monitoring ripening, such as fruit firmness and SSC with 2 > 0.89 and >0.70, respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…Iglesias and Echeverría [17] reported that peach fruit firmness alone is not a satisfactory minimum maturity index because it varies between nectarine cultivars, and for a given cultivar firmness varies in relation to fruit size, climatic conditions, and agronomical practices. Instead, background color is an informative harvest index as it reflects the chlorophyll content of the fruit [18]. Cascales et al [19] found that changes in peach fruit background color due to chlorophyll degradation are proportional to those perceived by a panel of assessors.…”
Section: International Journal Of Agronomymentioning
confidence: 99%
“…The chlorophyll absorption might be a certain method to determine the real maturation stage of the fruits. High correlations between the chlorophyll absorption and the level of maturation were reported for several fruits, including plums (Ziosi et al, 2008;Infante et al, 2011). Moreover, the absorption of chlorophyll could be a reliable method to determine the actual ripeness state of the plum fruit (Infante et al, 2011).…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…One of the options is the DA-Meter based on chlorophyll absorbance (index of absorbance difference), which allows sorting fruits into different groups according to their maturation [15,16]. However, because of large differences in fruit ripening-rate patterns and specific pericarp characteristics, the response is cultivar-dependent, and requires large investigation to properly calibrate the measure [17].…”
Section: Introductionmentioning
confidence: 99%